1982
DOI: 10.1073/pnas.79.10.3241
|View full text |Cite
|
Sign up to set email alerts
|

Human transferrin receptor: expression of the receptor is assigned to chromosome 3.

Abstract: Human chromosome 3 has been identified as responsible for expression of the transferrin receptor in mouse-human lymphocyte hybrids. The receptor was detected by immunoprecipitation with anti-human receptor antibody of "MI-labeled cells. This method also detected a similar 94,000-dalton protein in mouse cells. A radioimmunoassay developed for the human transferrin receptor measured 10% crossreactivity with the mouse protein. The two proteins were distinguished by NaDodSO4/ polyacrylamide gel patterns of partial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

1984
1984
1994
1994

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(12 citation statements)
references
References 31 publications
1
9
0
2
Order By: Relevance
“…The TR has been characterized biochemically (Enns & Sussman, 1981;Schneider et al, 1982) and also the gene for the human TR has been cloned recently and the primary structure determined (McClelland et al, 1984;Schneider et al, 1984). While the gene for both the human TR and transferrin has been localized to chromosome 3 (Goodfellow et al, 1982;Enns et al, 1982), this coincidence appears to be of no particular functional significance.…”
Section: Biochemical Characterization Of Membrane Transferrin Receptorsmentioning
confidence: 94%
See 2 more Smart Citations
“…The TR has been characterized biochemically (Enns & Sussman, 1981;Schneider et al, 1982) and also the gene for the human TR has been cloned recently and the primary structure determined (McClelland et al, 1984;Schneider et al, 1984). While the gene for both the human TR and transferrin has been localized to chromosome 3 (Goodfellow et al, 1982;Enns et al, 1982), this coincidence appears to be of no particular functional significance.…”
Section: Biochemical Characterization Of Membrane Transferrin Receptorsmentioning
confidence: 94%
“…For instance, the C-terminus region of the polypeptide was found to be facing the extracellular environment and the Nterminus domain, consisting of approximately 62 amino acids, represents the cytoplasmic tail of the receptor ( Figure). In general, secreted and transmembrane proteins studied thus far have been Sutherland et al (1981), Trowbridge and Omary (1981), Enns, Suomalainen et al (1982), Goodfellow et al (1982), Schneider et al (1982Schneider et al ( , 1984, McClelland, Kuhn and Ruddle (1984). O, High mannose oligosaccharide chain; O, complex oligosaccharide chain; ,~, acylated fatty acid moiety; ( ), estimated mol wt in kilodaltons; AA, approximate number of amino acids found to be synthesized with an N-terminus region facing the extracellular environment.…”
Section: Biochemical Characterization Of Membrane Transferrin Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier work of Naylor, et al (29) predicted that in mice Tf mapped to chromosome 9, a homologue of human chromosome 3. The genes encoding the Tf receptor and melanoma antigen p97 have also been assigned to chromosome 3 (30)(31)(32), and the Tf receptor gene has been localized to the 3q22 -+ ter region (33). A heretofore unmapped linkage group (34) consisting of ceruloplasmin, pseudocholinesterase-1, a2Hs-glycoprotein (and Tf) can now be mapped to chromosome 3. In summary, Tf cDNA has been identified and characterized from a human liver cDNA library.…”
Section: Resultsmentioning
confidence: 99%
“…With monoclonal antisera the transferrin receptor gene (T F R C ) could be assigned to chromosome 3 (Goodfellow et al, 1982), confirmed (Enns et al, 1982), and regionally mapped to SRO 3q23->qter (Jones et al, 1984;van de Rijn et al, 1983) . Homology of regions in mouse chromosome 9 and human chromosome 3, to which the aminoacylase 1 gene ACY1 and the beta-galactosidase 1 gene GLB1 have been assigned, as well as the mapping of the mouse transferrin gene (T F R ) to this region, raises the possibility that the structural loci for the transferrin receptor and for transferrin may also be linked in man (Goodfellow et al, 1982;Naylor et al, 1982).…”
Section: Chromosome 3 (Table II and Fig 2)mentioning
confidence: 99%